Island boy - Cooney, Barbara, 1917- (New York, NY : Trumpet Club, 1989)
Matthais grows from a little boy to a grandfather on a small island off the coast of New England.
The free end papers, on which map and text appear, are included in the page count.
Keywords: Islands -- Juvenile fiction; Growth -- Juvenile fiction; Islands -- Fiction; New England -- Juvenile fiction